2021
DOI: 10.1186/s43014-021-00057-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and nutritional characterization of modeled and optimized consumer-ready flakes from pseudocereal (Amaranthus viridis), high-protein soymeal and modified corn starch

Abstract: Flake is consumed in many parts of the world. Flakes are majorly prepared from cereals. However, most flakes are deficient in protein and some other healthful substances. High-protein soymeal is rich in protein, mineral, amino acids, antioxidants, and other healthful substances. Formulating flakes with high-protein soymeal would improve the health status of consumers. This work investigated consumer-ready flake from amaranth, high-protein soymeal, and modified corn starch produced under the optimized condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The vitamin B 6 content of the breakfast cereal flakes ranged from 1.40 to 3.85 mg/100 g. The values recorded in this study were higher than values of 0.52 to 0.85 mg/100 g reported on extruded snacks produced from sorghum and charamnya flour blends 30 . Meanwhile, Fasuan et al 34 reported a value of 1.81 mg/100 g for ready‐to‐eat flake from acha, sesame, and modified corn starch. Pyridoxine enhances nerve functioning and the formation of blood 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…The vitamin B 6 content of the breakfast cereal flakes ranged from 1.40 to 3.85 mg/100 g. The values recorded in this study were higher than values of 0.52 to 0.85 mg/100 g reported on extruded snacks produced from sorghum and charamnya flour blends 30 . Meanwhile, Fasuan et al 34 reported a value of 1.81 mg/100 g for ready‐to‐eat flake from acha, sesame, and modified corn starch. Pyridoxine enhances nerve functioning and the formation of blood 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…Kadar air terendah terdapat pada flakes dari G48 dengan TK30:TD70. Hasil penelitian lain dari Amrinola et al (2022) menyatakan bahwa flakes yang dihasilkan berkisar antara 8,65-10,27% dan produk flakes glutinous rice dan flakes high protein soymeal sebesar 8,96% (Fasuan et al, 2021). Flakes tepung kedelai tergerminasi tidak jauh berbeda dengan kedua penelitian tersebut namun sedikit lebih rendah.…”
Section: Kadar Air Flakesunclassified
“…Kadar protein ini lebih tinggi dibandingkan flakes yang dihasilkan oleh Amrinola et al (2022). Kadar protein flakes dari kedelai tergerminasi ini tidak berbeda jauh dengan kadar protein flakes yang dihasilkan oleh Fasuan et al (2021), yaitu sebesar 29,05%.…”
Section: Kadar Proteinunclassified
See 1 more Smart Citation
“…Starch accounts for approximately 40% of the nutrient requirements for broilers, and provides more than 50% of the metabolic energy, which plays an important role in maintaining glucose and lipid metabolism [1], as well as the stability of gut microbiota in poultry [2]. Starch can be classified into three types, which are usually named rapidly digestible starch, slowly digestible starch, and resistant starch (RS) [3].…”
Section: Introductionmentioning
confidence: 99%